Gummatous penile ulceration and generalised lymphadenopathy in homosexual man: case report. Issue 4 (August 1988) - Kitchen, V S; Cook, T; Doble, A; Harris, J R
Abstract : A case of granulomatous penile ulceration associated with generalised lymphadenopathy in a homosexual man aged 43 is presented. His serum gave positive results to tests for syphilis, but was negative for antibody to human immunodeficiency virus (HIV). His condition responded briskly to treatment with procaine penicillin, and we conclude that the clinical features were attributable to infection with Treponema pallidum.